The regional economic impact of oil and gas extraction in Texas. (December 2015) - Lee, Jim
Abstract: This paper empirically investigates the regional economic impact of oil and gas extraction in Texas during the recent shale oil boom. Regressions with county-level data over the period 2009–2014 support smaller multiplier effects on local employment and income than corresponding estimates drawn from popular input–output-based studies. Economic impacts were larger for extraction from gas wells than oil wells, while the drilling phase generated comparable impacts. Estimates of economic impacts are greater in a dynamic spatial panel model that allows for spillover effects across local economies as well as over time. Highlights: Economic impacts and multiplier effects differ between oil and gas wells in Texas. Interactions among local economies raise employment and income effects. Impacts persist over time, raising the long-run multipliers. Greater economic impacts from newly drilled wells than legacy wells.